Thermal regulation of photovoltaic modules using thermal energy storage units with PCMs - Soares, N. (2018)
High operating temperatures reduce the performance of commercial polycrystalline silicon photovoltaic (PV) devices by reducing the efficiency of solar to electrical energy conversion in the PV cells. This paper presents the major developments in the construction of a real-scale experimental apparatus to evaluate the efficiency improvement of PV systems by placing a movable thermal energy storage (TES) unit filled with free-form PCMs on the panels' back. In fact, the TES units are intended to control the temperature rise in the PV cells by taking advantage of the thermal regulation potential of PCMs during phase-change. The experimental setup is placed on the flat roof of the ADAI building, located in Coimbra, Portugal. It is composed by four PV modules, separately installed and individually monitored. One of the modules is taken as reference. Different TES units (with several configurations and filled with different PCMs with diverse phase-change temperature ranges) will be added to the other PV modules. The time evolution of the temperature of the PV modules will be compared with each other to measure the effective thermal regulation effect of the TES units. A data acquisition system for current, voltage and power monitoring and recording was developed with a LabVIEWTM program interface in order to compare the efficiency of the different PV/PCM systems throughout the day. A mobile peak power and I-V-curve measurement device for PV modules will be used to measure the short circuit current (ISC) and the open circuit voltage (VOC) of the PV panels. While ISC mostly depends on solar radiation, the VOC-value mainly depends on the temperature of the PV cells. Therefore, the time evolution of the VOC-value will be measured in order to determine the impact of PCMs in the efficiency improvement of the PV modules.